Efficiency of a New Combined Laser Therapy in Patients With Trophic Ulcers of Lower Extremities and Chronic Venous Insufficiency - Moskvin, Sergey Vladimirovich (J Lasers Med Sci, 2017)
Introduction: Treating patients with trophic ulcers (TUs) of venous etiology (VE) is a complicated socio-medical and economic problem. One of the ways to increase treatment efficiency can be a complex therapy, including combined laser action. Methods: The objective of this study was a comparative evaluation of the efficiency of traditional treatment methods in patients with chronic venous diseases of C6 class, and combined laser therapy (LT) according to a new method by LASMIK® device. External exposure was conducted on the 1-4 affected area during one session for 2 minutes per zone (pulsed mode, light pulse duration of 100-130 ns, wavelength 635 nm, by a matrix emitter consisting of eight laser diodes with a surface area of 8 cm2, at a distance of up to 7 cm, pulsed power 40 W). Intravenous laser blood illumination (ILBI) was conducted in continuous mode with a wavelength of 365-405 nm (UV-spectrum) and 520-525 nm (green spectrum) alternately, during 12 daily sessions, according to a special scheme. Results: The new method reduces time periods for wound surface cleansing from purulo-necrotic masses, stimulates proliferation and epithelialization processes by 2-2.7 times, compared with the conventional method. Conclusion: The high efficiency of a new combined LT has been demonstrated in the treatment of TU of VE in combination with traditional methods of patients’ medical treatment.